The influence of fashion blogs in the female consumer purchase decision process - Nogueira, Carla Cristine Vianna; Ferreira, Daniele de Oliveira; Arruda Filho, Emílio José Montero (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This article aims to analyze how female consumers are influenced by contents published in fashion blogs. To do so, it examines two blogs—Entre Topetes e Vinis, oriented towards the plus size public, and Garotas Estúpidas, of regular fashion—, by evaluating if the motivations of each public are hedonic or utilitarian according to their profile of consumption. The research has a qualitative nature and uses the netnographic method, which is based on investigating groups that participate in virtual communities and/or Internet discussion sites. The results show a great influence on the purchase decision process in the case of the plus size blog, focused on the users’ utilitarian values, while the regular blog activates a more hedonic relationship, serving as a source of information and as a form of group interaction. This scenario serves as a basis for companies to observe the stimuli and characteristics of each consumer, thus taking advantage of all the benefits that the social media researched herein offers to the fashion market today.